In order to solve the given system of equations, proceed as follow:
Multiply the first equation by 2:
(x - 2y = -5)(2)
2x -4y = -10
Next, subtract the second equation of the system to the previous equation:
2x - 4y = -10
-2x - 3y = -11
0 - 7y = -21
Solve the previous equation for y:
-7y = -21
7y = 21
y = 21/7
y = 3
Now, replace the previous result for y into the first equation of the system and solve for x:
x - 2y = -5
x - 2(3) = -5
x - 6 = -5
x = -5 + 6
x = 1
Hence, the solution for the given system of equations is the point (1,3)